Elections Integrity: Realizing Ultimate Concern and Electoral Justice - Yuli Purnama, Taufiq; Sigit Sapto Nugroho; Sarbini (Journal of Transcendental Law, 2023)
Democracy as a government by the people in which the supreme power is vested in the people and exercised directly by them or their elected representatives under a system of free elections. In general, democracy is often interpreted as a government by the people, for the people and of the people. The supreme power in a democratic system is in the hands of the people. Elections as a manifestation of a democratic state of law that provides space for competitive and periodic (sequential) elite circulation. Elections with integrity are determined by 3 prerequisites, namely (1) the integrity of the election organizers, (2) the integrity of the contestation (stages), and (3) the integrity of the election results. The implementation of elections with integrity is a will based on a noble concern (ultimate concern) for the achievement of quality and integrity elections as a manifestation of a democratic legal state. In addition to realizing a fair election (electoral justice) which encourages the holding of elections based on the principles of direct, free general, secret, honest and fair / luber jurdil (free and fair election), legal certainty (predictable procedure), election results according to voter choice (electoral integrity).